2011
DOI: 10.1128/ec.05097-11
|View full text |Cite
|
Sign up to set email alerts
|

Poly(A)-Specific Ribonuclease (PARN-1) Function in Stage-Specific mRNA Turnover in Trypanosoma brucei

Abstract: Deadenylation is often the rate-limiting event in regulating the turnover of cellular mRNAs in eukaryotes. Removal of the poly(A) tail initiates mRNA degradation by one of several decay pathways, including deadenylation-dependent decapping, followed by 5 to 3 exonuclease decay or 3 to 5 exosome-mediated decay. In trypanosomatids, mRNA degradation is important in controlling the expression of differentially expressed genes. Genomic annotation studies have revealed several potential deadenylases. Poly(A)-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Previous functional studies have shown that PARN is involved in several crucial physiological processes such as the meiotic maturation of frog oocytes [49], embryogenesis and stress response in plants [50,51] and stage-specific protein production in Trypanosoma brucei [52]. As for the cellular processes, PARN can regulate cell motility in mouse myoblasts [33], maturation of mammalian H/ACA box snoRNA [53], miRNA biogenesis [54] and DNA damage response (DDR) [31,32,55].…”
Section: Discussionmentioning
confidence: 99%
“…Previous functional studies have shown that PARN is involved in several crucial physiological processes such as the meiotic maturation of frog oocytes [49], embryogenesis and stress response in plants [50,51] and stage-specific protein production in Trypanosoma brucei [52]. As for the cellular processes, PARN can regulate cell motility in mouse myoblasts [33], maturation of mammalian H/ACA box snoRNA [53], miRNA biogenesis [54] and DNA damage response (DDR) [31,32,55].…”
Section: Discussionmentioning
confidence: 99%
“…For most mRNAs, removal of the poly(A) tail precedes degradation of the remainder of the transcript (Manful et al 2011). A typical mRNA degradation machinery is present: an exosome (Estévez et al 2001; a scavenger decapping enzyme (Banerjee et al 2009); an Xrn1 homolog, XRNA (Li et al 2006); PAN2/PAN3 (Schwede et al 2009); PARN (Milone et al 2004;Utter et al 2011); a CAF1/NOT complex composed of CAF1, CAF40, NOT1, NOT2, NOT3/5 (Schwede et al 2008); a CNOT11 homolog (Schwede et al 2008;Mauxion et al 2013); and CNOT10 (Färber et al 2013). Only a Dcp2-like decapping enzyme is missing (Schwede et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Also, we found that transcripts that have at least one instance of CoRM1970 are overrepresented in poly(A) + mRNA content of T. brucei cells that overexpress poly(A)-specific ribonuclease 1 (25), suggesting that CoRM1970-containing transcripts are also protected against deadenylation activity of this enzyme (Figure 2A). This is in line with previous reports showing that ELAV-like proteins can simultaneously bind to the ARE and poly(A) tail (46), and thus possibly protect the poly(A) tail of ARE-containing transcripts.…”
Section: Resultsmentioning
confidence: 93%
“…The motif name along with the structure/sequence is shown on the left, with each column representing one expression data set. The letters in brackets correspond to the reference publications that describe each experiment: a: (23), b: (26), c: (25), d: (21), e: (22). ( B ) Trypanosoma brucei genes (blue dots) are mapped on the first two principal components of 22 previously published expression data sets (21–27).…”
Section: Resultsmentioning
confidence: 99%